Analysis of penel drop-off on shear slip at flat slab in the animal hospital education building of the Faculty of Veterinary Medicine (RSHP-FKH), Udayana University - Tejadinata I Gusti Ngurah Agung Eka Arya; Maulana Nyoman Parthin Indra; Sinarta I Nengah; Triswandana I Wayan Gde Erick; Sarassantika Putu Ellsa (Journal of Infrastructure Planning and Engineering, 2023)
The Animal Hospital Education of the Faculty of Veterinary Medicine (RSHP-FKH) at Udayana University is located on Sesetan Main Road, Markisa Alley, No. 6, South Denpasar District, Denpasar, Bali. The building structure is planned with a modified flat slab design incorporating drop panels around the column areas. The purpose of this modification is to provide flexibility in spatial arrangement, facilitate the installation of mechanical and electrical systems, and indirectly meet the height requirements specified by the local regulations in Bali. The structural analysis of the Animal Hospital Education building at RSHP-FKH, Udayana University was conducted using the ETABS v.18 software, following the guidelines of the Indonesian National Standard (SNI). The analysis focused on the effect of drop panels on shear slip in the flat slab. The analysis aimed to determine the magnitude of deflection and its corresponding locations in the structure. The results of the analysis provide relevant information regarding the strength and stability of the building structure, ensuring that the RSHP-FKH building at Udayana University meets the established standards.